Electrocyclic Ring Opening of Charged cis-Bicyclo[3.2.0]heptadiene and Heterocyclic Derivatives. The Anti-Woodward−Hoffmann Quest (II) - Silva López, Carlos; Faza, Olalla Nieto; de Lera, Ángel R. (Journal of organic chemistry, 2009)
The ring opening reactions of fused cyclobutenes have been the subject of mechanistic debate for decades. Some reports have been published recently suggesting that, in some heterocyclic derivatives, the disrotatory anti-Woodward−Hoffmann mechanism might be responsible for the ring opening. We hereby show that the conrotatory pathway is still the lowest energy alternative for all cases examined, including push−pull substituted 2-thia-4-azabicyclo[3.2.0]hepta-3,6-dienes. Actually, we found that the disrotatory transition state exchanges roles with a double-bond isomerization depending on the substituents around the bicyclic structure.